2022
DOI: 10.3390/nano12213896
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Oxide-Poly(3,4-ethylenedioxythiophene) Nanocomposite as High-Performance Cathode for Aqueous Zn-Ion Batteries: The Structural and Electrochemical Characterization

Abstract: In this work the nanocomposite of vanadium oxide with conducting polymer poly(3,4-ethylenedioxythiophene) (VO@PEDOT) was obtained by microwave-assisted hydrothermal synthesis. The detailed study of its structural and electrochemical properties as cathode of aqueous zinc-ion battery was performed by scanning electron microscopy, energy dispersive X-ray analysis, X-ray diffraction analysis, X-ray photoelectron spectroscopy, thermogravimetric analysis, cyclic voltammetry, galvanostatic charge–discharge, and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, X-Ray Diff raction Method (XRD) aims to characterize the crystallography of a sample through the peaks formed at an angle of 2θ diff ractogram (Volkov et al, 2022). In this study, the 2θ angle read in the formation of the peak ranged from 0° to 80° shown in Figure 2.…”
Section: Carbon Characterization Based On Water Spinach Stemsmentioning
confidence: 97%
“…Furthermore, X-Ray Diff raction Method (XRD) aims to characterize the crystallography of a sample through the peaks formed at an angle of 2θ diff ractogram (Volkov et al, 2022). In this study, the 2θ angle read in the formation of the peak ranged from 0° to 80° shown in Figure 2.…”
Section: Carbon Characterization Based On Water Spinach Stemsmentioning
confidence: 97%
“…In this work, the structure, composition, and electrochemical performance of vanadium oxidebased composites with PEDOT obtained at two different temperatures of microwave-assisted synthesis have been studied for the first time. It was previously reported that such a modification method resulted in superior electrochemical performance [32,33]. The effect of the temperature of hydrothermal synthesis on the functional properties of the cathodes for aqueous zinc-ion battery was evaluated by different electrochemical techniques.…”
Section: Introductionmentioning
confidence: 99%